The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10509-012-1113-7
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionless cosmology

Abstract: Although it is well known that any consideration of the variations of fundamental constants should be restricted to their dimensionless combinations, the literature on variations of the gravitational constant $G$ is entirely dimensionful. To illustrate applications of this to cosmology, we explicitly give a dimensionless version of the parameters of the standard cosmological model, and describe the physics of Big Bang Neucleosynthesis and recombination in a dimensionless manner. The issue that appears to have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 119 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…In fact, several models incorporating non-minimal couplings between dark energy and the electromagnetic sector have already been proposed in the literature, as solutions to problems in contemporary cosmology [65][66][67][68][69]. Although a thorough analysis of the cosmological implications of the DE-UP has not yet been attempted, the cosmological implications of Λ ∝ α −6 e cosmology were investigated in [70,71], in the context of a time-varying fine structure constant.…”
Section: Additional Cosmological Implicationsmentioning
confidence: 99%
“…In fact, several models incorporating non-minimal couplings between dark energy and the electromagnetic sector have already been proposed in the literature, as solutions to problems in contemporary cosmology [65][66][67][68][69]. Although a thorough analysis of the cosmological implications of the DE-UP has not yet been attempted, the cosmological implications of Λ ∝ α −6 e cosmology were investigated in [70,71], in the context of a time-varying fine structure constant.…”
Section: Additional Cosmological Implicationsmentioning
confidence: 99%
“…Another aspect of the variation fundamental constants, which has been much discussed in the literature (see e.g., Dicke 1962;Duff 2002;Uzan 2003;Narimani et al 2012), is that only dimensionless combinations of constants can really be measured. Because of this, many previous studies have focussed on the parameter µ ≡ m e /m p .…”
Section: Beyond (α M E )mentioning
confidence: 99%
“…However, there have been other suggested scalings published, e.g., Narimani et al (2012) adopted α 5 , while Kaplinghat et al (1999) suggested a scaling motivated by the dependence of the effective recombination rate on temperature, yielding α 3.4 . We checked however that this difference in scaling has a subdominant impact on the spectra and that the results are essentially unmodified, whichever scaling we choose.…”
mentioning
confidence: 99%
“…The self-similar symmetry (SSS) model [40] describes the CMB with a symmetrical self-similar structure. The model consists of dimensionless values, because a physical constant with a dimension would not have universality [29]. Therefore, we define the fundamental dimensionless mass ratios of the proton mass m pr , electron mass m e , and Planck mass m Pl as follows:…”
Section: B Sss Modelmentioning
confidence: 99%
“…While the standard cosmological model assumes that Λ is invariant, recent observations in particle physics and cosmology indicate that Λ ought to be treated as a dynamical quantity rather than a simple constant [17][18][19][20][21][22][23][24][25][26][27][28]. In addition, dimensional analysis [29] and the action principle [30] suggest that Λ and G cannot vary independently. Therefore, a number of cosmological models incorporating variable Λ and G have subsequently been studied [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%